Analisis Penerapan Manajemen Risiko Usaha Lapangan Minisoccer Berbasis ISO 31000 - Nabila Syaharani; Aisyah Humayyrah; Indy Fauziah Hanifah; Ari Assrisan Sosh Mantoro; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines the implementation of ISO 31000:2018–based operational risk management at the Minisoccer Perbi field in Bandung. A descriptive qualitative approach was employed using observation, interviews, and documentation to identify, analyze, evaluate, and treat operational risks. The findings indicate that major risks include player injuries, slippery field conditions during rain, inadequate drainage, and disruption due to extreme weather. These risks significantly affect user safety, temporary operational shutdowns, and financial losses. Recommended mitigation measures include improving safety facilities, renovating drainage systems, implementing match-postponement procedures, and providing player insurance. Overall, Perbi’s risk management system aligns with ISO 31000 principles, yet lacks optimal documentation and digital monitoring. This study offers practical contributions for community sports facilities to enhance safety, operational effectiveness, and business sustainability.